2012
DOI: 10.1017/s0263034612000493
|View full text |Cite
|
Sign up to set email alerts
|

Fast electron beam with manageable spotsize from laser interaction with the tailored cone-nanolayer target

Abstract: An advanced cone-nanolayer target with nanolayers on both inside and outside of the hollow-cone tip is proposed. Twodimensional particle-in-cell simulations show that laser interaction with such cone-nanolayer targets can efficiently produce fast electron beams with manageable spotsize, and the beams can propagate for a relatively long distance in the vacuum beyond the cone tip.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Zheng et al proposed and simulated a "slice cone" target [29] attributing the accelerated electrons to a similar mechanism. 2D simulations on similar shaped nanobrush targets have also been published [30][31][32][33][34][35][36].…”
Section: B Target Designmentioning
confidence: 99%
“…Zheng et al proposed and simulated a "slice cone" target [29] attributing the accelerated electrons to a similar mechanism. 2D simulations on similar shaped nanobrush targets have also been published [30][31][32][33][34][35][36].…”
Section: B Target Designmentioning
confidence: 99%
“…For a flat solid foil target irradiated by the incident laser, the laser pulse is largely reflected at the plasma critical density. By contrast, a nanowire target which has a stack of thin plasma layers at subwavelength spacing grown on a thin metallic substrate (Cao et al 2010;Wang et al 2012;Yu et al 2012) is beneficial to generate more hot electrons. The complex geometry enables the laser pulse to interact for an extended distance with the inner volume of the target.…”
Section: Introductionmentioning
confidence: 99%
“…To optimize the interactions of laser pulses and targets, several novel targets with structured surface, such as metal nanobrushes [7][8][9][10][11][12][13][14][15], carbon nanotubes [16][17][18], silicon [19][20][21][22][23][24] and oxide nano/microwires [25] are proposed to improve the quality of laser-driven fast electron beams, proton acceleration and x-ray emission [15,26,27]. Many experiments [11][12][13][17][18][19] and relevant simulations [7,8,[28][29][30][31] on femtosecond laser facilities have demonstrated that tailored nano-array structures are helpful to enhance the absorption efficiency of laser energy as well as to guide the propagation of fast electrons. It is believed that the increased absorption depth, surface-to-volume ratio and high local electric fields of these kinds of targets can contribute to the enhancement of laser absorption, thus greatly enhancing the temperature of hot electrons and hard x-ray generation [7,11,15,32].…”
Section: Introductionmentioning
confidence: 99%